A framework for advancing the science of environmental justice along the international wildlife trade pathway - Arroyo-Quiroz, Inés; Gore, Meredith L.; Reaser, Jamie K. (Frontiers in Conservation Science, 2025)
The international wildlife trade can be a significant driver of biodiversity loss, as well as a facilitator of zoonotic disease transmission with pandemic potential. Environmental justice has never been more relevant to the wildlife trade as it is today. Yet, environmental justice has not been sufficiently mainstreamed into conservation science, nor practice. Here, we propose a framework for advancing the transdisciplinary science of environmental justice in the international wildlife trade context. The framework is organized via three interrelated domains: a) social justice, b) wildlife species justice, c) ecological justice. Each of these domains is described in terms of transdisciplinary questions that are intended to foster the translation of science of environmental justice for wildlife trade and should be tailored to cultural and historical contexts. It is our hope that the framework stirs open, transparent, mutually respectful discussions about justice between conservation researchers, practitioners, and the vast array of wildlife trade stakeholders.